2013
DOI: 10.2111/rem-d-13-00031.1
|View full text |Cite
|
Sign up to set email alerts
|

Wolf (Canis lupus) Predation Impacts on Livestock Production: Direct Effects, Indirect Effects, and Implications for Compensation Ratios

Abstract: Growing wolf (Canis lupus L.) populations in the US Rocky Mountain Region have increased conflicts between livestock production and wolf conservation. Given that the costs of large carnivore conservation are disproportionately borne by local livestock producers, the United States uses compensation for wolf damage to reduce conflicts and mediate negative attitudes toward the predators. Current compensation programs, however, only consider the direct effects of wolf predation. Indirect effects, such as wolf effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Indeed, predators could have a greater effect on prey demography through fear than through direct consumption of individual prey (Preisser et al 2005). For livestock on rangelands the indirect effects of predators are likely to include decreased conception rates and weaning weights (Howery and DeLiberto 2004;Steele et al 2013). On the other hand, apex predators dominate intraguild relations (Palomares and Caro 1999;Caro and Stoner 2003) such that a collapse in an apex predator population typically results in the phenomenon of mesopredator release (Prugh et al 2009;Ritchie and Johnson 2009), which can have negative implications for biodiversity conservation (Johnson et al 2006).…”
Section: Predationmentioning
confidence: 99%
“…Indeed, predators could have a greater effect on prey demography through fear than through direct consumption of individual prey (Preisser et al 2005). For livestock on rangelands the indirect effects of predators are likely to include decreased conception rates and weaning weights (Howery and DeLiberto 2004;Steele et al 2013). On the other hand, apex predators dominate intraguild relations (Palomares and Caro 1999;Caro and Stoner 2003) such that a collapse in an apex predator population typically results in the phenomenon of mesopredator release (Prugh et al 2009;Ritchie and Johnson 2009), which can have negative implications for biodiversity conservation (Johnson et al 2006).…”
Section: Predationmentioning
confidence: 99%
“…Conflict mitigation requires understanding how multiple factors interact in influencing livestock predation rates and the human-wolf conflict; factors such as the ecology and behavior of wolves (Mech and Boitani 2010), livestock attributes and handling (Mech et al 2000), wild prey availability (Meriggi et al 2011), costs for rural economies (Steele et al 2013), compensation and subsidy schemes , human attitudes (Stronen et al 2007), human-caused mortality (Wielgus and Peebles 2014), or even political interests (Chapron and López-Bao 2014). But wolf management should also integrate those policies with potential to affect all of the abovementioned factors, such as environmental and agriculture policies in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this can be the relatively recent focus on predation in these countries around national parks or animal refuges (Mishra 1997;Butler 2000;Rao et al 2002;Madhusudan 2003;Ikeda 2004;Michalski et al 2006;Gusset et al 2009;Tamang and Baral 2008;Abay et al 2011). A few of the studies on costs of livestock predation estimate both direct and indirect costs and show that the indirect cost can be of similar magnitude of order as the direct cost (Howery and DeLiberto 2004;Laporte et al 2010;Steele et al 2013;Ramler et al 2014). Schwabe et al (2001); the seven other studies are found in Häggmark-Svensson et al 2015h 2 studies on upland game (rabbit, pheasant, quail, grouse, wild turkey, and dove), 1 each on all and big game i All game j The value of an increase in the probability of bagging a deer by 1%…”
Section: Costs Of Wildlifementioning
confidence: 99%